Efficiency of energy consumption as a base for sustainable energy sector - Stasytyte, Viktorija; Ignotas, Anicetas (Business: Theory and Practice, 2016)
Lithuania, as many other EU countries, encounters key challenges in three energy sector fields: energy independence, energy sector competitiveness and sustainable energy sector development. Such situation is determined by historical and political conditions, as well as by limited internal energy resources. In such context an importance of energy consumption efficiency pursuing country energy sector sustainability is highlighted. By implementing the long-term goals and tasks a country may seek to increase the efficiency of energy production, distribution and consumption, as well as to increase energy production from renewable and waste energy sources. The main objective of the paper is to analyze the efficiency of energy consumption, the factors influencing energy sector competitiveness and sustainability, and to assess the development soundness of the use of renewable energy sources in Lithuania. The paper discusses the main EU legal documents and their provisions regulating energy sector, analyze energy production and consumption efficiency data in Lithuania and reveal the economic effect of the use of renewable energy sources in Lithuania.